Correlation between different LDL-R mutations and response to ab-PCSK9 therapy in a group of patient with genetic diagnosis of Familial Hypercholesterolemia. Preliminary report. (25th November 2020) - Buonaiuto, A; Gentile, M; Calcaterra, I.L; Giacobbe, C; Tripaldella, M; Forte, F; Iannuzzo, G; Di Minno, M.N.D; Fortunato, G; Rubba, P.O.F
Abstract: Introduction: Familial hypercholesterolemia (FH) is an autosomal dominant disease that leads to premature cardiovascular disease (CAD). The availability of ab-PCSK9 has changed the approach to therapy. Purpose: To evaluate the relationship between different types of mutations in LDLR gene and response to ab-PCSK9. Methods: 73 FH patients, 33 women and 40 men (53.9±13. yrs), in primary prevention (N=46) and secondary prevention (N=27), were recruited. This sample included patients with mutations in LDLR gene: heterozygotes for missense mutations (N=31), for null mutations (N=31), compound heterozygotes or homozygotes (N=11). At baseline, the whole sample had a maximally tolerated lipid lowering therapy (MT-LLT) without ab-PCSK9; 16 patients had MT-LLTs intolerance. After 160 days with ab-PCSK9 therapy we evaluated the achievement of a goal (LDL-C<70 mg/dL in primary prevention without Diabetes Mellitus, LDL-C<55 mg/dL). Results: After 160 days of therapy with ab-PCSK9 (45 patients on Alirocumab, 28 patients on Evolocumab) and MT-LLT, 29/73 patients (39.7%) of the whole sample achieve the goal of LDL-C. Of them 14/29 (48.2%) were in primary prevention, 15/29 (51.7%) in secondary prevention, no difference in achievement of the goal. We then evaluated the percent of patients achieving the goal of LDL-C: 15/31 (48.3%) patients with missense mutation and 14/31 (45.1%) patients with null mutation, no significant difference among groups; 0/11 compound heterozygotes or homozygotes; 3/16 (18.7%) MT-LLTs intolerance. The other main cardiovascular risk factors did not influence of the achievement the goal of LDL cholesterol. Conclusions: Lack of correlation between type of mutation in heterozygous FH patients and ab-PCSK9 therapy response; response was significantly poorest in patients with compound heterozygosis or homozygosis mutation as compared to heterozygotes; the intolerance to MT-LLT was significant in the achievement of the goal of LDL-C. Funding Acknowledgement: Type of funding source: None